Pengaruh Modal, Lama usaha, dan Teknologi terhadap Pendapatan UMKM Asosiasi Laundry Indonesia Pasca Pandemi Covid-19 di Kota Samarinda - Aminatul Barokah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This research aims to determine the effect of capital, length of business, and technology on the income of micro, small, and medium enterprises (MSMEs) that are members of the Indonesian Laundry Association (ASLI) in Samarinda City. The study employs a descriptive research design with a quantitative approach to provide a structured and measurable analysis of the relationships between variables. The sample consisted of 39 respondents selected using a non-probability sampling technique, ensuring representation of ASLI members within the study area. Data were collected through observation, structured interviews, and questionnaires, which were designed to capture detailed information regarding business characteristics, capital structure, technology adoption, and income levels. The collected data were analyzed using multiple linear regression to test both the partial and simultaneous effects of the independent variables on income. The results reveal that, partially, the capital variable does not have a significant effect on income, suggesting that access to or the amount of capital may not directly translate into higher earnings within this industry. Conversely, the length of business operation has a significant positive effect on income, indicating that experience and business maturity contribute to better financial performance. The technology variable, despite its importance in other sectors, does not show a significant partial effect on income in this context. However, when analyzed simultaneously, capital, length of business, and technology together have a significant effect on income, highlighting the importance of these factors in combination rather than isolation.This study contributes to the understanding of MSME performance determinants, particularly in service-based industries such as laundry businesses, and provides insights for policymakers and practitioners in developing targeted support strategies to enhance income sustainability.